Performance of stocker steers grazing smooth bromegrass at two stocking rates and dewormed with morantel tartrate - K.P. Coffey; Joseph L. Moyer; Lyle W. Lomas (Kansas Agricultural Experiment Station Research Reports, 1989)
Early-intensive grazing of smooth bromegrass reduced animal gains but improved gain/acre. Morantel tartrate reduced fecal nematode egg counts but had no effect on animal performance at either stocking rate
Keywords: Cattlemen' s Day; 1989; Kansas Agricultural Experiment Station contribution; no. 89-567-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 567; Beef; Performance; Stocker steers; Bromegrass; Morantel tartrate; stocking rates